Statements About the Pervasiveness of Behavior Require Data About the Pervasiveness of Behavior - Speelman, Craig P.; McGann, Marek (Frontiers in Psychology, 2020)
Despite recent close attention to issues related to the reliability of psychological research (e.g., the replication crisis), issues of the validity of this research have not been considered to the same extent. This paper highlights an issue that calls into question the validity of the common research practice of studying samples of individuals, and using sample-based statistics to infer generalisations that are applied not only to the parent population, but to individuals. The lack of ergodicity in human data means that such generalizations are not justified. This problem is illustrated with respect to two common scenarios in psychological research that raise questions for the sorts of theories that are typically proposed to explain human behaviour and cognition. The paper presents a method of data analysis that requires closer attention to the range of behaviours exhibited by individuals in our research to determine the pervasiveness of effects observed in sample data. Such an approach to data analysis will produce results that are more in tune with the types of generalisations typical in reports of psychological research than mainstream analysis methods.